A Study on Distance Learning: A Developmental Leap towards Smart Education in Smart Cities - MITHUN R; Roopadarshini S (RADINKA JAYA UTAMA PUBLISHER, 2024)
The research investigates the transformative implications of integrating distance learning within the framework of smart cities, unraveling its role in reshaping educational paradigms. Within the dynamic context of urban development, the study explores the symbiotic relationship between distance learning and smart cities, aiming to elucidate how this fusion contributes to inclusive, adaptable, and future-oriented educational ecosystems. Emphasizing the significance of distance learning in democratizing education, the study delves into its ability to transcend geographical barriers, offering flexible and personalized learning experiences. Through an extensive literature review and a comprehensive methodology involving surveys and diverse stakeholder perspectives, the study examines smart education's multifaceted role in smart city development, emphasizing technological integration, innovation, and socioeconomic empowerment. Furthermore, the research delineates the developmental leap facilitated by distance learning within smart cities, highlighting its role in advancing inclusivity, lifelong learning, and sustainability goals. The intricate relationship between distance learning, smart learning, and smart cities is analyzed, showcasing their interconnectedness in fostering educational evolution within technologically advanced urban landscapes. Additionally, the study underscores the comprehensive advancements in smart education by amalgamating innovative technological integration, refined pedagogical practices, and robust infrastructural frameworks. The research concludes by identifying key findings, highlighting advancements, and addressing persisting challenges in infrastructure, connectivity, and data privacy, signaling areas necessitating improvement. Ultimately, the study underscores the pivotal role of distance learning in propelling smart education within smart cities, culminating in the creation of inclusive, accessible, and technologically enriched educational landscapes.